Numerical modeling of the prestressing losses in prestressed concrete beams by modal analysis method - Hamza Djeffal; Mohamed Nadir Amrane (Journal of Applied Engineering Science and Technology, 2018)
In this paper, a numerical modal analysis method is carried out to investigate the effectof cable strain loss on the natural frequencies in prestressed concrete beams. A simply supportedconcrete beam is modeled using the commercial finite element code ABAQUS. The beam iscomposed of concrete and prestressing strands. Firstly, a general geometrically nonlinear staticanalysis is carried out on the beam in order to obtain the camber deflection under differentprestressing magnitudes. The obtained equilibrium configuration is then used to perform a linearand nonlinear modal analysis. Thereby, a three dimensional finite element C3D8 is used for theconcrete in combination with a damaged plasticity model (CDP) are considered. Whereas, theprestressing strands are modeled with an embedded T2D2 truss element. The obtained resultsshow a good agreement with previous numerical and experimental works in literature.Furthermore, the study showed that the safety of prestressed beams depend mainly on the levelof prestressing load.